A tetramer micelle: the smallest aggregation number corresponding to the vertex number of regular polyhedra in platonic micelles. Issue 6 (5th January 2018) - Fujii, Shota; Takahashi, Rintaro; Ha, Lee Ji; Sakurai, Kazuo
Abstract : Sulfonatocalix[4]arene-based amphiphiles form monodisperse tetramer micelles whose aggregation number is the smallest corresponding to the vertex number of regular polyhedra. Abstract : In this paper, we describe the construction of tetramer micelles based on the idea of "Platonic micelles" whose aggregation number ( N agg ) matches the vertex number of regular polyhedra and exhibits the monodispersity and discreteness in the N agg .